(untitled) (Boletin Médico de Postgrado, 2020)
A non-experimental, transversal, descriptive study was conducted to establish the epidemiological characteristics of accidents in the home of 112 patients between 2 and 13 years of age who attended the Atención Médica Inmediata (AMI) of the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga between December 2018 and January 2019. Most patients are preschoolers (46%), male sex (71%) and from urban areas (59.8%). In most cases, mothers were older than 30 years (39.2%), with secondary education (44.6%) and homemakers (69.6%). The majority of fathers were older than 30 years (54.5%), with primary education (37.5%) and worked outside the home (90.1%). Most caregivers were older than 30 years (67%) and relatives of the child (93%). Accidents occurred predominantly on Friday (18.8%), from 1 to 6:59 pm (46%) and in the yard (36.6%). Most frequent type of accident were falls (34.9%), followed by burns (25%) and poisoning (21.4%). This study allowed us to know the epidemiological characteristics of accidents in the home and provides data for decision-making and the development of prevention protocols.